The Effect of Trichocompost Application Based on Sago Pulp Against the Growth of Cucumbers (Cucumis sativus L.) - Kamaruddin, Nisma; Irwan Halid; Naima Haruna (SINTA Journal (Science, Technology, and Agricultural), 2025)
This research aims to investigate the response of various types of vegetable plants, namely cucumber (Cucumis sativus L.), to the application of trichocompost made from sago pulp. The use of this organic fertilizer is raised as a solution to address modern agricultural challenges such as soil fertility degradation and dependence on chemical fertilizers. Sago pulp, as an abundant agro-industrial waste, is processed into trichocompost using the antagonistic fungus Trichoderma sp., which not only functions as a decomposer but also as a biological control agent against soil-borne diseases. Based on the research results, it can be concluded that the application of Sago Tricocompost has varying effects depending on the type of plant. In cucumber plants, the application of tricocompost, particularly at the highest dosage (P3), consistently shows a very significant effect on vegetative growth (plant height) and harvest yield (fruit weight and production per hectare). This indicates that sago waste tricocompost is very effective as an organic fertilizer to enhance cucumber productivity, likely due to its nutrient content and the microbial activity of Trichoderma that supports growth.